OPTIMASI PELAPISAN KITOSAN UNTUK MENINGKATKAN MASA SIMPAN PRODUK BUAH-BUAHAN SEGAR POTONG - -, Nurhayati; Hanum, Tirza; Rangga, Azhari; -, Husniati (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
This study was aimed to obtain the optimal concentration of chitosan and the longest shelf life of melon, watermelon and pineapple slices. The experiment was factorial, and arranged in a completely randomized block design with 3 replications. The first factor: the concentration of chitosan consisted of 5 levels (0%, 0.5%, 1%, 1.5% and 2%). The second factor was 4 level duration of storage (0 day, 4 days, 8 days and 12 days). Homogenity and additivity of the data were tested using Bartlet and Tukey tests, then they were analyzed using analysis of variance and followed by least significant difference test (LSD). The best results for melon fruit slices were obtained at a concentration of 1% chitosan 4 days of storage with the number of yeast and mold plate count 8.03 x 102 colonies/g and 9.03 x 103 colonies/g respectively. The best results for watermelon fruit slices were at a concentration of 1.5% chitosan 4 days storage time with the number of yeast and mold plate count 6.06 x 102 colonies/g and 6.66 x 102 colonies/g respectively. The best results of pineapple fruit slices obtained at a concentration of 1.5% chitosan 4 days storage time with the number of yeast and mold plate count 9.56 x 102 colonies/g and 1.76 x 102 colonies/g respectively. Keywords: fruit slices, melon, mold, pineapple , storage time, yeast, water melon